Isothermal Oxidation Behavior of Ferritic Oxide Dispersion Strengthened Alloy at High Temperatures - Eddy Agus Basuki; Nickolas Adrianto; Rahmadhani Triastomo; Akhmad Ardian Korda; Tria Laksana Achmad; Fadhli Muhammad; Djoko Hadi Prajitno (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
This paper discusses the oxidation behaviors of ODS steel alloy of Fe-16Cr-4Al-1Ni-0.4ZrO2 at 700 ℃, 800 ℃, and 900 ℃. X-ray diffraction (XRD) as well as X-ray mapping in a scanning electron microscope were used to characterize the oxidation behavior of the samples. The rate of oxidation was measured based on the thickness of the oxide formed on the surface of the samples. Six types of oxides were identified in all ODS Fe-16Cr-4Al-1Ni-0.4ZrO2 alloy samples after the oxidation tests, dominated by Fe2O3, Fe3O4, Cr2FeO4, AlFeO3, Al2FeO4, and AlFe2O4. The oxidation kinetics of ODS Fe-16Cr-4Al-1Ni-0.4ZrO2 steel at 700, 800, and 900 ℃ followed logarithmic oxidation rate behavior.